2009
DOI: 10.1111/j.1439-0418.2008.01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on the predation rate of Anthocoris nemorum (Het.: Anthocoridae) on cabbage aphids (Hom.: Aphididae)

Abstract: The temperature‐dependent predation by Anthocoris nemorum L. (Het.: Anthocoridae) on second instar Brevicoryne brassicae L. (Hom.: Aphididae) at constant temperatures of 12, 15 and 20°C increased linearly with temperature with a mean (±SE) consumption of 6.9 (±0.8), 9.28 (±1) and 15.9 (±0.8) respectively. The estimated lower temperature threshold for predation (T0) was 6.4°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It is a polyphagous species reported to feed on Cacopsylla pyri (L.) (Hemiptera: Psyllidae) and Brevicoryne brassicae (L.) (Hemiptera: Aphididae) [ 56 , 85 , 86 ]. This is the first report showing that it predates upon M. hellenica .…”
Section: Resultsmentioning
confidence: 99%
“…It is a polyphagous species reported to feed on Cacopsylla pyri (L.) (Hemiptera: Psyllidae) and Brevicoryne brassicae (L.) (Hemiptera: Aphididae) [ 56 , 85 , 86 ]. This is the first report showing that it predates upon M. hellenica .…”
Section: Resultsmentioning
confidence: 99%
“…Others, however, found decreased or unchanged density (Roy et al 2004, Adler et al 2007, reduced adult survival (Ma et al 2004), or increased time and resources dedicated to avoiding heat stress (Ma and Ma 2012). Some studies found that predation rates increase with temperature (Jalali et al 2009, Simonsen et al 2009), whereas others have found that attack rates for some predators peak near ambient temperatures (Khan and Khan 2010) or only increase with temperature when the prey are highly mobile (Vucic-Pestic et al 2011).…”
Section: Introductionmentioning
confidence: 99%